Prospective community programme versus parent-driven care to prevent respiratory morbidity in children following hospitalisation with severe bronchiolitis or pneumonia. Issue 4 (24th February 2020) - Byrnes, Catherine Ann; Trenholme, Adrian; Lawrence, Shirley; Aish, Harley; Higham, Julie Anne; Hoare, Karen; Elborough, Aileen; McBride, Charissa; Le Comte, Lyndsay; McIntosh, Christine; Chan Mow, Florina; Jaksic, Mirjana; et al.
Abstract : Background: Hospitalisation with severe lower respiratory tract infection (LRTI) in early childhood is associated with ongoing respiratory symptoms and possible later development of bronchiectasis. We aimed to reduce this intermediate respiratory morbidity with a community intervention programme at time of discharge. Methods: This randomised, controlled, single-blind trial enrolled children aged <2 years hospitalised for severe LRTI to 'intervention' or 'control'. Intervention was three monthly community clinics treating wet cough with prolonged antibiotics referring non-responders. All other health issues were addressed, and health resilience behaviours were encouraged, with referrals for housing or smoking concerns. Controls followed the usual pathway of parent-initiated healthcare access. After 24 months, all children were assessed by a paediatrician blinded to randomisation for primary outcomes of wet cough, abnormal examination (crackles or clubbing) or chest X-ray Brasfield score ≤22. Findings: 400 children (203 intervention, 197 control) were enrolled in 2011–2012; mean age 6.9 months, 230 boys, 87% Maori/Pasifika ethnicity and 83% from the most deprived quintile. Final assessment of 321/400 (80.3%) showed no differences in presence of wet cough (33.9% intervention, 36.5% controls, relative risk (RR) 0.93, 95% CI 0.69 to 1.25), abnormal examination (21.7% intervention, 23.9% controls, RR 0.92, 95% CI 0.61 to 1.38) or Brasfield score ≤22 (32.4% intervention, 37.9% control, RR 0.85, 95% CI 0.63 to 1.17). Twelve (all intervention) were diagnosed with bronchiectasis within this timeframe. Interpretation: We have identified children at high risk of ongoing respiratory disease following hospital admission with severe LRTI in whom this intervention programme did not change outcomes over 2 years. Trial registration number: ACTRN12610001095055.